An investigation of the flexure-torsion flutter characteristics of aerofoils in cascade. - Lilley, G. M. (College of Aeronautics, Cranfield, 1952)
Part 1 of this report describes the results obtained from a series of tests on the flexure-torsion flutter characteristics of cascades of similar aerofoils having symmetrical sections. Continues … Part 2 of this report is a review of the theoretical studies on oscillating aerofoils in cascade. Continues …